Glutathione S-transferase M1, T1, and P1 Polymorphisms and Ovarian Cancer Risk: A Meta-Analysis. Issue 5 (1st June 2010) - Economopoulos, Konstantinos P.; Sergentanis, Theodoros N.; Vlahos, Nikos F.
Abstract : Introduction: Cytosolic glutathione S -transferase (GST) comprises multiple isoenzymes that catalyze reactions between glutathione and lipophilic compounds with electrophilic centers, resulting in the neutralization of toxic compounds, xenobiotics, and products of oxidative stress. Several studies have examined whether GST polymorphisms (GSTM1 null/present genotype, GSTT1 null/present genotype, and GSTP1 Ile105Val) represent risk factors for ovarian cancer, as they all may denote reduced enzyme activity. This meta-analysis aimed to examine the associations between the aforementioned polymorphisms and ovarian cancer risk. Methods: The MEDLINE database was searched up to September 2009 using the appropriate terms. Case-control studies with no mutually overlapping populations were selected. Pooled odds ratios (ORs) were appropriately derived from fixed-effects or random-effects models. Meta-regression with publication year was also performed. Results: Eight studies regarding GSTM1 null polymorphism status (2357 cases and 3044 controls), 6 studies concerning GSTT1 null polymorphism (1923 cases and 2759 controls), and 3 studies on GSTP1 Ile105Val were included in the meta-analysis. The GSTM1 null genotype was not associated with an increased risk for ovarian cancer (pooled OR, 1.031; 95% confidence interval, 0.867-1.226; random effects). The GSTT1 null genotype was not associated with an increased ovarian cancer risk (pooled OR, 0.934; 95% confidence interval, 0.804-1.086; random effects); similarly, no significant associations were demonstrated for GSTP1 Ile105Val. Conclusions: The examined GSTM1, GSTT1, and GSTP1 genotype polymorphisms do not seem to confer any additional risk for ovarian cancer. Given that the studies included in this meta-analysis involve mainly white populations, these results cannot be extrapolated on other populations, and additional data are needed for future race-specific analyses.